Answer:
B
Explanation:
(6
z)^3
6^3 is 226
*(x^2)^3= x^6 (5*3= 15)
*when there are exponents being raised to a power, the exponents are multiplied
**(z^1)^3= z^3 (3*1= 3)
** all numbers are raised to the 1st power (unless otherwise noted x^2, 5^4 2^2, etc)
So the top would end up being 226x^6z^3
Now, since this number is over 4x^4z^2, you need to divide 226x^15z^3 by 4x^4z^2
**divide like terms**
226/4= 54
***x^15/ x^4= x^x^11
*** when you divide exponents, you subtract the bottom number from the top, in this case:
15-4
that equalls 11
So x^11
you do the same for z:
z^3/z^2= z^1 or z (3-2=1 )
You put it all together and you end up with
54x^11z
******** If there are any mistakes I'm really sorry!!******